Trigger Learning Outcomes through Contextual Teaching and Learning Assisted Performance Assessment - Ni Nyoman Parmithi; I Wayan Eka Mahendra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
This study aims to map the effect of CTL learning assisted by performance assessment on biology learning outcomes in terms of student creativity. This research was conducted on class XI students of SMA N 1 Kuta Utara in the academic year 2018/2019 by involving a sample of 76 samples taken by the technique of multi-stage random sampling. Learning CTL assisted by performance assessment as an independent variable, creativity as a moderator variable, and biology learning outcomes as a dependent variable. Biology learning outcomes data were captured by tests and creativity data were captured by questionnaires that had been tested for validity and reliability coefficients. The collected data were analyzed using parametric statistics in the form of two-way Anova, which previously carried out prerequisite tests in the form of data normality test and variance homogeneity test. The results of this study indicate that: biology learning outcomes of students who follow CTL assisted by performance assessment are better than biology learning outcomes of students who follow conventional learning and there is an interaction between learning approaches and the level of students' creativity in their influence on biology learning outcomes. To obtain more optimal learning outcomes, it is recommended to consider the level of student creativity.Keywords: CTL, performance assessment, learning outcomes